Jorge el curioso va a la biblioteca = Curious George visits the library / ilustrado en el estilo de/illustrated in the style of H.A. Rey por/by Martha Weston ; traducido por/translated by Carlos E. Calvo. - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Weston, Martha (Boston : Houghton Mifflin Harcourt, 2011)
Jorge el monito curioso visita la biblioteca por la primera vez.
George is lucky to arrive at the library just in time for story hour. But it's not easy for a little monkey to sit still too long. From selecting books to getting his very own library card, George's day at the library makes reading fun.
Parallel text in Spanish and English.
Keywords: Libraries -- Fiction; Curious George (Fictitious character) -- Fiction; Monkeys -- Fiction; Spanish language materials -- Bilingual